The European Union and Party Politics in Central and Eastern Europe
XVI, 260 p.
Keywords: This book examines the influence of the EU on party politics in the ten 'new' EU countries from a variety of perspectives and using a range of empirical sources. The book thus makes an original and distinctive contribution both to contemporary EU studies and to the literature on CE party systems and party development.